2003
DOI: 10.1016/s0309-1740(02)00062-1
|View full text |Cite
|
Sign up to set email alerts
|

The tenderisation of shin beef using a citrus juice marinade

Abstract: The tenderisation of shin beef using a citrus juice marinade Author links open overlay panelR.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
82
0
3

Year Published

2003
2003
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 98 publications
(93 citation statements)
references
References 15 publications
8
82
0
3
Order By: Relevance
“…Tenderness is an important quality parameter in the meat, and US was reported as reduced the hardness of bovine muscles, when applied at 24 kHz and 12 W/cm 2 [22]. Also, acidic marinade favors the tendering of meat, as was reported by Burke and Monahan [23] in shin beef.…”
Section: Effect Of Treatments On Whcmentioning
confidence: 83%
“…Tenderness is an important quality parameter in the meat, and US was reported as reduced the hardness of bovine muscles, when applied at 24 kHz and 12 W/cm 2 [22]. Also, acidic marinade favors the tendering of meat, as was reported by Burke and Monahan [23] in shin beef.…”
Section: Effect Of Treatments On Whcmentioning
confidence: 83%
“…The most recent were dedicated to beef (Aktas, Aksu, & Kaya, 2003;Burke & Monahan, 2003;Desmond & Troy, 2001;Ke, Huang, Decker, & Hultin, 2009), turkey (Goli, Ricci, Bohuon, Marchesseau, & Collignan, 2014) and poultry meats (Yusop, O'Sullivan, Kerry, & Kerry, 2010). Other authors have considered alkaline marinating; this process increases meat pH from its initial post-mortem ultimate value but not necessarily above pH 7.…”
Section: Introductionmentioning
confidence: 99%
“…Studies (Berge et al, 2001;Burke & Monahan, 2003) have shown that marination or injection of beef with organic acids (acetic, citric, lactic) enhances tenderness. Lawrence, Dikeman, Hunt, Kastner, & Johnson (2003) evaluated calcium ascorbate, calcium chloride, and calcium lactate for their effects on color, lipid oxidation, tenderness, and sensory attributes of beef strip loins.…”
Section: Introductionmentioning
confidence: 99%